Gestión administrativa del Almacén Montoya - Miño Triguero, Genesis Yamilex (2021)
Administrative management is in decline due to the lack of a pertinent study that determines the optimal distribution of functions in the workers of the Montoya warehouse, this research has been carried out since since 2018 there are difficulties among workers due to the lack of internal space and discomfort among workers due to various causes that have arisen over time, as well as lack of motivation, lack of training as well; When considering the carelessness on the part of the boss at the time of controlling the activities of the workers due to the fact of checking the merchandise that goes out and collecting, all these causes as a whole have created a deficient administrative management by not controlling the planning, organization, direction and control processes. Work stress is another important factor that oppresses the entire operation of the "Montoya Warehouse", this is caused on several occasions by excessive workloads, poor motivations, insufficient salary and even by activities that carry great responsibility. As a whole, there is a deficient level of productivity on the part of the worker, that labor relations are null and that there is labor disorganization and in itself it leads to the non-fulfillment of the objectives set by the warehouse, achieving dissatisfaction about the performance and the profitability of the warehouse. For all the causes mentioned above, the present case study was carried out.